Carbon monoxide and nitric oxide as coneurotransmitters in the enteric nervous system: Evidence from genomic deletion of biosynthetic enzymes - Xue, L. (The National Academy of Sciences, 2000)
Nitric oxide (NO) and carbon monoxide (CO) seem to be neurotransmitters in the brain. The colocalization of their respective biosynthetic enzymes, neuronal NO synthase (nNOS) and heme oxygenase-2 (HO2), in enteric neurons and altered intestinal function in mice with genomic deletion of the enzymes (nNOS(Δ/Δ) and HO2(Δ/Δ)) suggest neurotransmitter roles for NO and CO in the enteric nervous system. We now establish that NO and CO are both neurotransmitters that interact as cotransmitters. Small intestinal smooth muscle cells from nNOS(Δ/Δ) and HO2(Δ/Δ) mice are depolarized, with apparent additive effects in the double knockouts (HO2(Δ/Δ)/nNOS(Δ/Δ)). Muscle relaxation and inhibitory neurotransmission are reduced in the mutant mice. In HO2(Δ/Δ) preparations, responses to electrical field stimulation are nearly abolished despite persistent nNOS expression, whereas exogenous CO restores normal responses, indicating that the NO system does not function in the absence of CO generation.